Therapeutic In Vivo Gene Editing Achieved by a Hypercompact CRISPR‐Cas12f1 System Delivered with All‐in‐One Adeno‐Associated Virus - Cui, Tongtong; Cai, Bingyu; Tian, Yao; Liu, Xin; Liang, Chen; Gao, Qingqin; Li, Bojin; Ding, Yali; Li, Rongqi; Zhou, Qi; Li, Wei; Teng, Fei (Advanced science, 2024)
CRISPR‐based gene therapies are making remarkable strides toward the clinic. But the large size of most widely used Cas endonucleases including Cas9 and Cas12a restricts their efficient delivery by the adeno‐associated virus (AAV) for in vivo gene editing. Being exceptionally small, the recently engineered type V‐F CRISPR‐Cas12f1 systems can overcome the cargo packaging bottleneck and present as strong candidates for therapeutic applications. In this study, the pairwise editing efficiencies of different engineered Cas12f1/sgRNA scaffold combinations are systemically screened and optimized, and the CasMINI_v3.1/ge4.1 system is identified as being able to significantly boost the gene editing activity. Moreover, packaged into single AAV vectors and delivered via subretinal injection, CasMINI_v3.1/ge4.1 achieves remarkably high in vivo editing efficiencies, over 70% in transduced retinal cells. Further, the efficacy of this Cas12f1 system‐based gene therapy to treat retinitis pigmentosa in RhoP23H mice is demonstrated by the therapeutic benefits achieved including rescued visual function and structural preservation. And minimal bystander editing activity is detected. This work advances and expands the therapeutic potential of the miniature Cas12f1 system to support efficient and accurate in vivo gene therapy. A hypercompact mini‐CRISPR system suitable for all‐in‐one AAV delivery, CasMINI_v3.1/ge4.1, is identified to achieve highly efficient and accurate in vivo gene editing. This Cas12f1‐based system is employed to cure retinal degeneration in a mouse model of genetic blindness in this study, suggesting its promising applications for in vivo gene therapy.